Penerapan Metode Analytical Hierarchy Process (AHP) dalam Sistem Pendukung Keputusan Pemilihan Supplier di Sebuah Klinik Swasta - Khoirunnisa, Khoirunnisa; Susanti, Lia (Journal Global Technology Computer, 2025)
The problem faced is the calculation is still done manually so that it causes errors in determining the selection of suppliers based on the cheapest price, discounts given, payment terms and speed of product delivery then there is no decision support system in the supplier determination process at the Medika Insani Clinic in Bekasi City because it still uses a conventional system and not a computerized system. The purpose of designing a decision support system for selecting suppliers is to make it easier for clinic owners to choose suppliers and the calculation process is computerized using the AHP method. The method used in this study is the Analytical Hierarchy Process in solving the problems that have been studied. The results obtained in this study are to produce an accurate report of the best supplier selection data at the Medika Insani Clinic so that it can help in making strategies in the future. The application system that has been designed is suitable for use in the supplier selection process at the Medika Insani Clinic because it is in accordance with the needs, so it can facilitate the administration in the data input process and report creation.